(untitled) (Journal of the College of Education for Women, 2019)
The current research aims to assess the Brief Book of the Modern and Contemporary History of Asia from the perspective of the students in the Department of History, University of Baghdad. The study is carried out in Iraq and the research group has included students of the Department of History in the College of Education–Ibn Rushd and the College of Education for Women- University of Baghdad. The chosen sample of the assigned research consisted of (72) students from third stage in the Department of History, which equals (0.38%) of the total group members amounted (188) female and male students representing (40) students from the College of Education–Ibn Rushd, and 32 students from the College of Education for Women. The researcher has addressed an open question to a sample of 20 reviewers of students in this department representing (0.11) of the total group originally gathered to make their remarks on the Brief Book of the Modern and Contemporary History of Asia, which is intended to be taught in 2014 within the curriculum prepared by the Ministry of Higher Education and Scientific Research. In the light of the responses and reviews of the assigned research group , the method of this research involved the (questionnaire) consisting of 40 assessing items which are classified to six fields such as: Introduction of the book, General aims, Teaching contents, Teaching activities, Technical direction, Preparing and composing the Brief Book of the Modern and Contemporary History of Asia.